2011
DOI: 10.12659/msm.881389
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trends with Improvement in Quality of Life after TVT, TVT O and Burch Colposuspension Procedures

Abstract: SummaryBackgroundComparison of the quality of life (QoL) trends after TVT, TVT O and Burch colposuspension (BCS) procedures and comparison of long-term subjective and objective outcomes.Material/MethodsThe study included 215 women who underwent a TVT, TVT O or BCS procedure. We monitored QoL after each procedure and the effect of complications on the QoL as assessed by the IQOL questionnaire over a 3-year period.ResultsThe study was completed by 74.5% of women after TVT, 74.5% after TVT O, and 65.2% after BCS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
1
1
0
1
Order By: Relevance
“…In our study, TOT was found more superior over Burch operation in providing SUI. Although there are some studies supporting the results of our study in the literature (21,22), a study showed that Burch colposuspension surgery is more successful than TOT operation (23).…”
Section: Discussionsupporting
confidence: 65%
“…In our study, TOT was found more superior over Burch operation in providing SUI. Although there are some studies supporting the results of our study in the literature (21,22), a study showed that Burch colposuspension surgery is more successful than TOT operation (23).…”
Section: Discussionsupporting
confidence: 65%
“…De los 11 artículos encontrados y depurados, 4 muestran diferencias significativas a favor de lograr mejor calidad de vida en las mujeres intervenidas con la técnica de cintas libres de tension 27,30,34,35 , 4 artículos no mostraron diferencias significativas en la calidad de vida entre los dos procedimientos 28,31,32,35 , 2 artículo mostró diferencias significativas a favor de la colposuspención de Burch 28,31 y un artículo no mostró diferencias entre los dos procedimientos, sin embargo evidenció que el mejor predictor asociado a mejorar la calidad de vida es la edad 36 .…”
Section: Discussionunclassified
“…Quality of life is a goal for all treatments and is usually decreased in chronic diseases [ 49 – 52 ]. Contrary to most other studies, we did not find evidence of decreased quality of life in our CFS population.…”
Section: Discussionmentioning
confidence: 99%